Pengaruh Sistem Informasi Manajemen Terhadap Efektivitas Kerja Staf Administrasi di SMK Negeri 1 Sangatta Utara - Azizzah Asma Al Husna; Faelasup Faelasup; Miftakhul Rizal Mubaidilla (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of Management Information Systems (MIS) on the effectiveness of administrative staff work at SMK Negeri 1 Sangatta Utara in 2025, involving 20 respondents. The method used is quantitative field research with data collection techniques in the form of observation, questionnaires, and documentation. The analysis was carried out through simple linear regression using SPSS 26. The results show a very strong relationship between MIS and work effectiveness with a correlation value of 0.859 and a determination value of 73.8%. The regression equation Y = 13.538 + 0.769X shows that MIS significantly increases work effectiveness, as evidenced by t count 7.116> t table 2.100.